An Interior-Point Solver for AC Optimal Power Flow Considering Variable Impedance-Based FACTS Devices - Bo Liu (IEEE, 2021)
This work proposes a full AC optimal power flow (ACOPF) model considering variable impedance-based flexible AC transmission system (FACTS) devices, in which the reactance of lines are introduced as decision variables to minimize system operation costs, power losses, and load shedding costs. This work is motivated by increasing interest in using FACTS and Distributed FACTS (D-FACTS) devices to address system operational and cyber-security concerns in the presence of renewable energy, such as line congestion relief, power loss reduction, load curtailment reduction, and moving target defense. The proposed ACOPF model can be utilized by system operators to achieve economic and cyber-security benefits simultaneously. In addition, we build and make publicly available an open-source MATPOWER-based interior-point solver for the proposed ACOPF model through rigorously deriving the gradient and Hessian matrices of the objective function and constraints. Numerical results on an IEEE 118-bus transmission system and an IEEE 69-bus distribution system show the validity of the proposed ACOPF model as well as the efficacy of the developed interior-point solver.